The Influence of Financial Literacy and Financial Management on the Financial Performance of MSMEs - Meldianus J Nabas; Aminah Aminah; Fausiah Fausiah; Azwin Hariyanto Cinta; Andi Novita Paramitha (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the influence of financial literacy and financial management on the financial performance of Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a strategic role in the national economy, but still face various financial management challenges that affect their low business performance. The research method used is a quantitative approach with survey techniques. Data was collected through questionnaires distributed to MSME actors and analyzed using multiple linear regression. The study finds that financial literacy has a positive and significant effect on the financial performance of MSMEs. In addition, financial management has been shown to have a positive, significant effect on financial performance. Simultaneously, financial literacy and financial management have a significant effect on the financial performance of MSMEs. These findings indicate that improving understanding and adopting good financial management practices are essential to enhancing MSME performance in a sustainable manner